Influence of dietary biosynthesized zinc oxide nanoparticles on broiler zinc uptake, bone quality, and antioxidative status - Mohd Yusof, Hidayat; Abdul Rahman, Nor’Aini; Mohamad, Rosfarizan; Zaidan, Uswatun Hasanah; Samsudin, Anjas Asmara (Multidisciplinary Digital Publishing Institute, 2022)
A total of 180 broiler chickens (Cobb500) were randomly allotted to five experimental groups consisting of six replicates and six birds in each pen. Each group was fed a basal diet supplemented with 100 mg/kg ZnO (control) and 10, 40, 70, and 100 mg/kg ZnO NPs for 35 days. Resultantly, Zn uptake and accumulation in serum, breast muscle, tibia bone, and liver were linearly and significantly (p < 0.05) increased with increasing dietary ZnO NPs supplementation at 100 mg/kg compared to the control group (dietary 100 mg/kg ZnO), implying effective absorption capacity of ZnO NPs. This was followed by lower Zn excretion in feces in broilers fed ZnO NPs compared to controls (p < 0.05). Furthermore, dietary ZnO NPs at 40, 70, and 100 mg/kg levels improved broiler tibia bone morphological traits, such as weight, length, and thickness. Similarly, tibia bone mineralization increased in broilers fed ZnO NPs at 100 mg/kg compared to the control (p < 0.05), as demonstrated by tibia ash, Zn, Ca, and P retention. Antioxidative status in serum and liver tissue was also increased in broilers fed dietary ZnO NPs at 70 and 100 mg/kg compared to the control (p < 0.05). In conclusion, dietary ZnO NPs increased Zn absorption in broiler chickens and had a positive influence on tibia bone development and antioxidative status in serum and liver tissue, with dietary ZnO NPs supplementation at 70 and 100 mg/kg showing the optimum effects.